Flow State: Menaklukan Hal Mustahil? - M. Haeru Anwar; Masduki Asbari (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to find out Haeru Anwar's perspective from the 1 Hari Success Youtube channel entitled "Flowstate conquers what is impossible". In this study, the researcher used a descriptive qualitative method by taking notes because the source of the data was obtained by listening to oral narratives. The results of this study explain what they feel when trying to conquer a challenge with feelings of joy and curiosity until they reach their goal. This article is defined as a person's ability to do a job or activity by balancing the difficulties they have to overcome so that they always become the best or optimal version of themselves.